Effect of casting and rolling process parameters on solidification welding line of magnesium alloy - Huang, Zhiquan; Lai, Hongyu; Zhou, Haibo; Guo, Hao (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
Process of horizontal twin roll casting magnesium alloy was analyzed by numerical simulation. Taking solidification welding line in cast rolling area as research object, the characteristic change of solidification welding line caused by casting rolling temperature, casting rolling speed, and roll heat transfer capacity and its influence on the forming process of casting rolling area were analyzed. The results show that increasing casting temperature, casting speed or reducing heat transfer capacity of roll can make solidification welding line shift to exit of casting rolling zone. Increasing casting temperature and casting speed will increase difference between middle and edge of the solidification welding line along casting direction and heat distribution of whole slab is more uniform. However, effect of improving heat transfer capacity of roll is completely opposite. According to this, optimum process parameters of casting and rolling magnesium alloy with plate thickness of 6 mm are put forward to reduce probability of edge crack.